2022
DOI: 10.1039/d2ra01546c
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric performance enhancement of eco-friendly Cu2Se through incorporating CB4

Abstract: Thermoelectric performance enhancement in a liquid-like material Cu2Se by introducing CB4 nanopowders based on the hydrothermal method and hot-pressing technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…The PF of the Cu/Se = 2.12 sample is higher than that of the other samples, and its maximum value is 4.12 μW cm –1 K –2 at 210 °C. Table presents the thermoelectric properties of different types of Cu 2 Se materials as well as other materials. , It can be found that the maximum power factor of the present Cu 2 Se thin film can be compared to the value of the reported Cu 2 Se, including thin films and bulk. , , However, compared with other p-type systems, the value of Cu 2 Se thin film has still been low and still needs to further improved by doping and microsturcuture manipulation.…”
Section: Resultsmentioning
confidence: 99%
“…The PF of the Cu/Se = 2.12 sample is higher than that of the other samples, and its maximum value is 4.12 μW cm –1 K –2 at 210 °C. Table presents the thermoelectric properties of different types of Cu 2 Se materials as well as other materials. , It can be found that the maximum power factor of the present Cu 2 Se thin film can be compared to the value of the reported Cu 2 Se, including thin films and bulk. , , However, compared with other p-type systems, the value of Cu 2 Se thin film has still been low and still needs to further improved by doping and microsturcuture manipulation.…”
Section: Resultsmentioning
confidence: 99%
“…Metal chalcogenides, such as Cu 2 Te/Cu 2 Se/Cu 2 S and Ag 2 Se/ Ag 2 S/Ag 2 Te, are mixed ionic-electronic conductors. [55][56][57][58][59] In these materials, the mobile ions can induce static and dynamic disorders, which can cause a strong disruption of phonon and give rise to a "phonon-liquid" behavior. [60] Meanwhile, the nonmobile rigid sublattice provides conduction paths for electrons and holes, which makes it an electron-crystal behavior.…”
Section: Te Materials With Electrons/holes As Charge Carriersmentioning
confidence: 99%
“…One of the most common selenide-based TE materials is Cu 2 Se, owing to its low cost, high theoretical zT near room temperature and easy fabrication as a thin film, which is excellent for applications in flexible, wearable electronics. [74] Cu 2 Se has been synthesized via a variety of processes, including pulsed laser deposition, [74] electrodeposition [75] and sintering, [76] among other techniques. [77,78] One of the more common techniques for fabricating thin-film TE materials is magnetron sputtering, owing to its uniformity, simplicity and precision.…”
Section: Selenidesmentioning
confidence: 99%